As I understand it, L'Hopital Rule comes from Cauchy's Generalised Mean Value Theorem, which states that if 2 functions, $f(x)$ and $g(x)$ are continuous and differentiable over the interval $[a,b]$ and $(a,b)$ respectively, then $∃$ $c∈[a,b]$ such that $$(f(b)-f(a))/(g(b)-g(a))=(f'(c))/(g'(c))$$

Now if $f(x)$ and $g(x)$ are arbitrary functions, why shouldn't L'Hopital Rule hold once the function is no longer indeterminate? Is there something I didn't see in the proof?

  • $\begingroup$ Do you mean that $b\to a$ (to ensure that $c\to a$)? $\endgroup$ – A.Γ. Aug 5 '18 at 7:52
  • 1
    $\begingroup$ Consider the limit of $\frac{3x^2}{2x}$ where x is tends to 1.Now putting $x=1$ we have the value $3/2$.But if we apply L'Hospital it will give us wrong answer! $\endgroup$ – Sufaid Saleel Aug 5 '18 at 7:54
  • $\begingroup$ @A.Γ. I'm not sure what you mean. From my understanding of Cauchy's Mean Value Theorem, a and b are boundaries you define for a function, and c is a point on the function where the relationship stated applies. $\endgroup$ – Yip Jung Hon Aug 5 '18 at 7:59
  • $\begingroup$ @SufaidSaleel Yes, that's true. But I don't understand why you have to stop applying L'Hopital Rule once the function is determinate. $\endgroup$ – Yip Jung Hon Aug 5 '18 at 8:00
  • $\begingroup$ @YipJungHon L'Hopital rule apples to limits. It is not clear what limit that you mean in the question. $\endgroup$ – A.Γ. Aug 5 '18 at 8:05

When $\lim_{x\to a}f(x)=\lim_{x\to a}g(x)=0$, then we can apply Cauchy's theorem:$$\frac{f(x)}{g(x)}=\frac{f(x)-f(a)}{g(x)-f(a)}=\frac{f'(c)}{g'(c)},$$for some $c$ and therefore$$\lim_{x\to a}\frac{f'(x)}{g'(x)}=L\implies\lim_{x\to a}\frac{f(x)}{g(x)}=L.$$But if $\lim_{x\to a}f(x)\neq0$ or $\lim_{x\to a}g(x)\neq0$, this argument doesn't apply anymore.

Of course, this doesn't actually prove that we can't apply L'Hopital's rule then. What proves that is the existence of counter examples.


I usually motivate L'hospital with Taylor series (or linear approximation if it's early in the course.) See that (using $a=0$ for convenience)

$$\lim_{x\to 0} \frac{f(x)}{g(x)} = \lim_{x\to 0} \frac{f(0) +f'(0)x+f''(0)x^2/2+\cdots}{g(0)+g'(0)x+g''(0)x^2/2+\cdots}.$$

If both $f(0)=0$ and $g(0)=0$, this becomes

$$\lim_{x\to 0} \frac{f'(0)x+f''(0)x^2/2+\cdots}{g'(0)x+g''(0)x^2/2+\cdots}.$$

But if they are not both $0$, then I can't do this step. Then I can cancel one $x$ in the fraction to get

$$\lim_{x\to 0} \frac{f'(0)+f''(0)x/2+\cdots}{g'(0)+g''(0)x/2+\cdots},$$

and we can repeat this reasoning until we hit a derivative that's not $0$ at $0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.